Microstructure modulation of hard carbon derived from long-flame coal to improve electrochemical sodium storage performances - Hai-Tao Zeng; Wei-Wei Kang; Bao-Lin Xing; Guang-Xu Huang; Qiang Li; Han Hu; Fang-Le Su; Jian-Bo Jia; Chuan-Xiang Zhang (Fuel Processing Technology)
Widely sourced precursors for hard carbon with high performances are still a major challenge for industrializing sodium-ion batteries. Herein, long-flame coal was adopted as the precursors to prepare hard carbon by carbonization at different temperatures, and the influences of carbonization temperatures on the microstructure together with electrochemical properties of hard carbon were systematically investigated. With elevating carbonization temperature, carbon layer spacing, defect concentration and C − O, CO functional groups of hard carbon all gradually decrease. The hard carbon prepared at 1500 °C (BHC-1500) demonstrates 38 % of the pseudo-graphite carbon with an average carbon layer spacing of 0.360 nm, a specific surface area of 31.2 m2/g and appropriate defect concentration (ID1/IG of 1.50). As anode active materials, BHC-1500 possesses a specific capacity of 254 mAh/g at 20 mA/g with initial coulombic efficiency of 79 %, a rate performance of 24.8% in 20-1000 mA/g, a capacity retention of 72 % after 1000 cycles at 500 mA/g, suggesting the excellent electrochemical sodium storage performances, which may be concerned with the highest proportion of pseudo-graphite carbon, appropriate carbon layer spacing, functional groups and defect concentration. The ex-situ XRD test confirms sodium storage mechanism of “adsorption-intercalation/filling” in hard carbon. This work can provide new ideas for clean utilization of long-flame coal and developing high performances anode active materials for SIBs.